Analysis of Risk Factors and Quality of Antenatal Care (ANC) in Pregnant Women with Preeclamsia in Ajung District, Jember Regency - tunsiah, tunsiah; Utami, Wiwien Sugih (Journal of Agromedicine and Medical Sciences, 2025)
In 2023 and 2024 Jember Regency had the highest maternal mortality rate (MMR) in East Java. Preeclampsia (PE), a form of hypertension during pregnancy, is the second leading cause of MMR after postpartum hemorrhage. This study aimed to analyze the risk factors and quality of antenatal care (ANC) for pregnant women with preeclampsia at the Ajung Community Health Center in Jember Regency. The study employed a retrospective cohort design. The study sample consisted of 55 pregnant women with preeclampsia from the Ajung Community Health Center between 2020 and May 2025. . A two-sample independent t-test was used to analyze differences in risk factors among women with preeclampsia statistically. An ordinal regression test determined the relationship between preeclampsia risk factors and ANC quality. The results revealed 49 cases of preeclampsia occurring at or after 34 weeks of gestation and six cases occurring before 34 weeks. A significant difference was found in maternal age as a risk factor for preeclampsia. Most of the ANC quality in the study sample was very poor (62.5%), with maternal age and mean arterial pressure (MAP) being the main influencing factors. Age-related risk factors differed among pregnant women with preeclampsia and a relationship was found between maternal age, MAP, and ANC quality.